Assessing climate impacts and risks of ocean albedo modification in the Arctic. Issue 5 (13th May 2016) - Mengis, N.; Martin, T.; Keller, D. P.; Oschlies, A.
Abstract: The ice albedo feedback is one of the key factors of accelerated temperature increase in the high northern latitudes under global warming. This study assesses climate impacts and risks of idealized Arctic Ocean albedo modification (AOAM), a proposed climate engineering method, during transient climate change simulations with varying representative concentration pathway (RCP) scenarios. We find no potential for reversing trends in all assessed Arctic climate metrics under increasing atmospheric CO2 concentrations. AOAM only yields an initial offset during the first years after implementation. Nevertheless, sea ice loss can be delayed by 25(60) years in the RCP8.5(RCP4.5) scenario and the delayed thawing of permafrost soils in the AOAM simulations prevents up to 40(32) Pg of carbon from being released by 2100. AOAM initially dampens the decline of the Atlantic Meridional Overturning and delays the onset of open ocean deep convection in the Nordic Seas under the RCP scenarios. Both these processes cause a subsurface warming signal in the AOAM simulations relative to the default RCP simulations with the potential to destabilize Arctic marine gas hydrates. Furthermore, in 2100, the RCP8.5 AOAM simulation diverts more from the 2005–2015 reference state in many climate metrics than the RCP4.5 simulation without AOAM. Considering the demonstrated risks, we conclude that concerning longer time scales, reductions in emissions remain the safest and most effective way to prevent severe changes in the Arctic. Key Points: Arctic Ocean albedo modification offsets Arctic climate trends only temporarily Compensatory oceanic heat fluxes result in an Arctic Ocean subsurface warming On longer time scales emission reduction is more effective in staying close to today's climate state